1989
DOI: 10.1111/j.1365-2338.1989.tb00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of bacterial wilt of fodder grasses1

Abstract: In order to explain the occurrence of very severe or more moderate wilt of grasses attacked by Xanthomonas campestris pv. graminis, various observations on the factors possibly influencing the epidemics of the disease are summarized in this article. Although natural vectors exist, the main means of transmission is certainly mowing tools. Resistance of the plants can be genetically predetermined or induced by non‐pathogenic phyllosphere bacteria, if these are inoculated at the same time as the pathogen and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…This indicates that young plants of perennial ryegrass are more susceptible to X.c.graittinis than old plants, which agrees with the result reported by Schmidt (1989). However, there was no difference in the rate of colonization of the plant by X.c.grantiiris when inoculating plants of different age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that young plants of perennial ryegrass are more susceptible to X.c.graittinis than old plants, which agrees with the result reported by Schmidt (1989). However, there was no difference in the rate of colonization of the plant by X.c.grantiiris when inoculating plants of different age.…”
Section: Discussionsupporting
confidence: 93%
“…Egli et al (1975) reported that the disease usually became noticeable in the field at the heading stage, when young leaves started to curl and wither without showing copious spots or lesions. Schmidt (1989) indicated that young seedlings of fodder grasses were particularly susceptible to X.c.grtriiiirzis. On the other hand, Leyns et al (1987) found' that very young plants of Loliiuti pereiirie L. cv.…”
Section: Introductionmentioning
confidence: 98%
“…Bacteria were detected in dead and dry leaves in this study. Schmidt (1989) also found bacteria in dry grass kept for 1 year at room temperature. Channon and Hissett (1984) reported that infection could take place through roots growing in infested soil.…”
Section: Discussionmentioning
confidence: 79%
“…Channon and Hissett (1984) reported that ryegrass cultivars varied in their susceptibility. Schmidt (1989) also reported resistance between cultivars of grass. In this study we found that a few plants of ryegrass and timothy still looked healthy when the others in the same pot had died, which indicates that there were differences in susceptibility among individual plants.…”
Section: Discussionmentioning
confidence: 95%
“…The flagellum has been reported to primarily function in epiphytic biofilm formation and to enable the bacteria to move towards suitable entry points [49]. As Xtg is primarily transmitted by contaminated mowing tools [50], flagellar motility seems not essential for the pathogen’s lifestyle. The same transmission strategies are likely to be valid among all forage grass affecting X. translucens pathovars, such as pv.…”
Section: Discussionmentioning
confidence: 99%